Proceedings of a National Workshop on Building Partnership, Strengthening Capacities and Developing Forest Resources Thru Community Based Forest Management, Angeles City, Philippines, August 6-7, 2002 - Hartanto, H.; Evangelista, R. (CIFOR and Philippines Department of Environmental and Natural Resources (DENR), 2002)
CIFOR initiated its research program on Adaptive Collaborative Management (ACM) in the Philippines in 1999. The results of ACM work in two Community Based Forest Management (CBFM) sites over a period of 3 years have been very positive and promising. At this workshop, CIFOR attempted to share the experience and lessons learnt with different audiences at different levels. Besides reviewing the results of ACM, this workshop also attempted to identify different strategies and approaches applied by different initiatives and projects in CBFM and to provide recommendations to improve the existing CBFM framework and policies. The wealth of experience and expertise of the workshop participants were also tapped to review and improve three CBFM-related regulations. The workshop showed that there are still many challenges and problems in CBFM that need to be addressed in the future so that CBFM can really benefit local communities and improve forest conditions in the country. Despite differences in the strategies and approaches used by the different projects, there were several common elements given attention to by these different projects. These include collaboration among stakeholders, monitoring, learning and incremental adjustments, and complexity. All these elements were embraced by Adaptive Collaborative Management (ACM) approach.